2023
DOI: 10.3390/nu15112619
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of a Low-Carbohydrate High-Fat Diet on Laboratory Parameters in Women with Lipedema in Comparison to Overweight/Obese Women

Abstract: The aim of this study was to evaluate alterations in blood parameters after a low-carbohydrate high-fat (LCHF) diet in women with lipedema in comparison to overweight or obese women. A total of 115 women were classified into two groups: the lipedema group and the overweight/obesity group. Both study groups followed the caloric-restricted LCHF diet for 7 months. A total of 48 women completed the study. A reduction in body weight was observed in both study groups. A significant decrease in triglycerides and an i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Even though LCD and ketogenic diets have been shown to increase low-density lipoprotein cholesterol in the general population [44] and female patients with lipedema [45], beneficial effects of these diets have been reported on glucose, liver function, triglycerides, and highdensity lipoprotein cholesterol in female patients with lipedema adopting an LCD for 7 months [45].…”
Section: Discussionmentioning
confidence: 99%
“…Even though LCD and ketogenic diets have been shown to increase low-density lipoprotein cholesterol in the general population [44] and female patients with lipedema [45], beneficial effects of these diets have been reported on glucose, liver function, triglycerides, and highdensity lipoprotein cholesterol in female patients with lipedema adopting an LCD for 7 months [45].…”
Section: Discussionmentioning
confidence: 99%
“…Most of the project results are yet to be published, except for 1 study on the lymphoscintigraphic alterations in the lower limbs 44 and 1 paper on the impact of the LCHF diet on blood parameters. 34 In this study, women diagnosed with lipedema (n = 45, with a mean age of 41.00 ±13.32 years) and women with lifestyle-induced overweight/obesity (n = 43, with a mean age of 44.95 ±13.90 years) who agreed to complete self-administered questionnaires evaluating disability, anxiety and depression symptoms were included. The women in both study groups were recruited from January 2021 to May 2022, and each woman's participation in the study was voluntary.…”
Section: Methodsmentioning
confidence: 99%
“…However, it should be noted that the low-carbohydrate high-fat diet (LCHF), which is rich in vegetable oils, has been shown to not only decrease leg volume in lipedema but also alleviate pain in adipose tissue. 33,34 Therefore, the addition of further essential oils may enhance the effects of the LCHF diet. Searching for new methods of treating lipedema is especially desirable since there is no cure for this entity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Emerging evidence has shown that modifying the proportion of macronutrients in the diet can help to improve multiple metabolic diseases, such as obesity, type 2 diabetes, and non-alcoholic fatty liver disease. 14,15 For example, a low-carbohydrate dietary pattern, characterized by carbohydrate proportion ranging from 20% to 26% of the total energy intake, has been reported to lower fat accumulation in the liver. Some extremely low-carbohydrate dietary patterns with a 10% or less carbohydrate calorie proportion, termed the ketogenic diet, have been shown to improve fatty liver.…”
Section: Introductionmentioning
confidence: 99%